Emergência auto-organizada sensório-motora/afetiva do tempo neurofenomenológico - Jesus, Johnny Marques de [UNESP] (2018)
In this work we will to evaluate the nature and implications of the thesis that phenomenolgical time is a emergent/self-organizing neural, embodied, active and situated phenomena. The idea here is to analyse what understanding of phenomenological time comes out from a possible neural/embodied/active/situated (for short, NEAS) perspective. What does it mean to conceive the hypothesis that subjectively lived time is a dynamic-complex structure that emerges from and contributes to the regulation of the self-organization of the global temporal system of the pragmatic and situated body? What are the fundamental theoretical lines that can be delineated and investigated so to make possible such hypothesis and which lines of argumentation can provide substantiation, verification and justification of such hypothesis? In order to prepare the terrain of this research, we propose a historical-philosophical paradigm provided by Guyau's model of psychological time, and later to correlate it with philosophical/psychological/neurological models of temporal processing/experiencing, with contemporaneous models about the situated/pragmatic embodiment of lived time and with contemporary models about cognition, emotion, action, and mind that, while not directly focused on the modeling of lived time, are relevant to our case. In this context, we first propose 6 propositions as the axis of conceptual coordinates for our arguments: (1) The affective temporality is structurally articulated with sensorimotor temporality; (2) from the primordial affective-motor temporal structures emerges neurophenomenological time; (3) the emergence of neurophenomenological time from, and as regulator of, the global workspace dynamics (space of informational integration Φ) implies that it exerts top-down and lateral constrains on the more basic affective-sensorimotor temporalities, contributing to the uncertainty reduction in the trajectory of active-body-in-the-world, through its contribution to the formation of more complex affective-motor patterns; (4) When the animal is processing temporal information in the environment, it can only do that if it process self-related temporal information, or proprioespecific temporal information indicating the individual existence of itself as opposed to the existence of external individuals and events. (4.1) Such bodily individuality is not given in egoic isolation, but is also a spatiotemporal constitution operated by the dynamics of the animalenvironment system; (5) A proto-narrative me-ness or ipseity is produced in the continuous temporal passive synthesis of bodily affective states at lower scale of temporal integration (the episodic time scale proposed by Lewis (2000)); (5.1) But this proto-narrative also involves proprioceptive/kineasthetic relf-related processing. Then bodily spatiotemporal self-individuation is a process of self-related temporal integration by synthesis of sucessive affective/proprioceptive/kinaesthetic states; (6) The primordial pragmatic time is a dynamics based on a circular causality between an affective-motor intentionality of time (in the phenomenological sense of referential directionality) and a form of self-referential synthesis of spatiotemporal bodily states constituting a primordial anoetic me-ness.